Digital Technologies and Artificial Intelligence: evidence of their effectiveness in education (Innovaciones Educativas, 2023)
The incorporation of digital technologies (DT) in educational processes is a reality, especially after the COVID-19 crisis and the expansion of Artificial Intelligence (AI). But still, the use of these technologies raises questions, above all, regarding their effectiveness in educational terms. This editorial article aims to reflect on the role of technologies in general, and AI in particular, in the current educational context. To this end, it examines international evidence on the subject for different educational levels. This review considers the most commonly used tools, modalities and pedagogical strategies that best accompany the use of these technologies in education. Finally, concrete ideas are proposed to effectively integrate the different DT and to understand the transversal role of AI, both in the teaching-learning and administrative processes, so that this can benefit the roles involved.
Keywords: Education; education system; digital technology; digitalization; artificial intelligence